Implementation of Digital Science and Literacy Teaching in Developing Science Literacy in Middle School Students in Indonesia - Mardiani, Eri; Mokodenseho, Sabil; Matiala, Tiara Fathulmila; Limbalo, Syifa Sumayyah Azzahrah; Mokodompit, Nesa Yuliska (The Eastasouth Journal of Learning and Educations, 2024)
This research investigates the impact of science teaching methods and digital literacy on the development of science literacy among junior high school students in Indonesia. A quantitative analysis employing structural equation modeling (SEM-PLS) was conducted on a sample of 150 students. Descriptive statistics revealed moderate science literacy levels, preferences for hands-on experiments, and a high proficiency in digital literacy. SEM-PLS results demonstrated significant positive relationships between science teaching methods, digital literacy, and science literacy. The bootstrapping analysis confirmed these relationships, emphasizing the importance of both factors in shaping science literacy outcomes. The model exhibited a strong fit, and coefficients indicated substantial explanatory and predictive power for Developing Science Literacy. These findings contribute to the understanding of effective educational strategies for science literacy in the Indonesian context.